The international banking system capital adequacy, core businesses and risk management - Lessambo, Felix I. (Palgrave MacMillan, 2013)
Provides a comprehensive and detailed understanding and analysis of banking businesses and their worldwide operations. Banks have become 'too big to fail', and too complex-to-manage in their inbound and outbound operations. This book gives the relevant details, approaches, and answers to these complex financial issues